FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI NILAM DI DESA TOLOLE KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Asgar, Muhammad; Muis, Abdul; Sulaeman, Sulaeman (AGROTEKBIS, 2019)
This research intends to identiy factor of wide area, cuttings, urea fertilizer, and labor that affects the production of patchouli in Tolole village Ampibabo Sub-district Parigi Moutong Regency. This research was conducted in Tolole village Ampibabo Sub-district Parigi Moutong Regency. This research was conducted on July 2017, 30 respondents of patchouli farmer were selected through census method. Production analysis used is Coob-Douglas. The result of this research showed that F counted is 10.274> Ftable 2.76 of ? = 5% which means that null hypothesis (H0) is rejected, and then the variable of wide area, cutting, urea fertilizer, and labor simultaneously affects the production of patchouli in Tolole village. Partially, the wide area and labor variable do not affect the production, while cutting and the use of urea fertilizer variable affects the production patchouli inTolole village Ampibabo Sub-district Parigi Moutong Regency.